Profit and More: Catholic Social Teaching and the Purpose of the Firm - Abela, Andrew V. (Journal of business ethics, 2001)
The empirical findings in Collins and Porras' study of visionary companies, Built to Last, and the normative claims about the purpose of the business firm in Centesimus Annus are found to be complementary in understanding the purpose of the business firm. A summary of the methodology and findings of Built to Lastand a short overview of Catholic Social Teaching are provided. It is shown that Centesimus Annus' claim that the purpose of the firm is broader than just profit is consistent with Collins and Porras empirical finding that firms which set a broader objective tend to be more successful than those which pursue only the maximization of profits. It is noted however that a related finding in Collins and Porras, namely that the content of the firm's objective is not as important as internalizing some objective beyond just profit maximization, can lead to ethical myopia. Two examples are provided of this: the Walt Disney Company and Philip Morris. Centesimus Annus offers a way to expose such myopia, by providing guidance as to what the purpose of the firm is, and therefore as to what kinds of objectives are appropriate to the firm.